THE EFFECTIVENESS OF THE SEDIMENT UTILIZATION EDUCATION MODEL AS AN ALTERNATIVE CONSTRUCTION MATERIAL FOR THE COASTAL COMMUNITY OF LAKE LIMBOTO - Desei, Frice L.; Purnamawati, Purnamawati; Abdul Gani, Hamsu (Jurnal Vokasi Keteknikan, 2025)
This study aims to analyze the effectiveness of the educational model in increasing the use of sediment as an alternative construction material for the coastal communities of Lake Limboto. The educational model developed is based on a participatory approach, practical training, and community-based socialization. The research method used is a quantitative approach with a pre-test and post-test design to measure changes in people's understanding and skills. The results of the study show that the applied education model significantly improves the knowledge and skills of the community in utilizing sediment as a construction material. Thus, this model can be an effective educational solution in supporting sustainable development in the coastal area of Lake Limboto.